The Role of the South African Pentecostal and Charismatic Church in Sustainable Development: Focusing on Safety and Security - Mangaliso Matshobane (Pharos Journal of Theology, 2023)
South Africa has one of the highest crime rates in the world, rated at number 4 globally and number 1 in the continent of Africa. Recently, the minister of Police in South Africa, Bheki Cele, revealed that violent crimes are extremely high with reported rape cases standing at an alarming 9516 between April-June 2022 while murders stand at 6424 in the same period. The question is what causes such a growth in crime but more importantly what role is played by PentecostalCharismatic churches in alleviating crime which negatively affects development in the country? A literary analysis of the nexus of crime and religion, buttressed by the case study of 2 megachurches who are part of South African Pentecostal and Charismatic churches (SAPCC), located in areas that are considered as hotspots of violent crimes, is used in this paper. The main objective of the article is to investigate the role of SAPCC in crime prevention and to position them as strategic role players in the realisation of Sustainable Development Goals with a focus on safety and security. This study proposes a decolonial theoretical framework based on the African proverb: ‘It takes a village to raise a child’, as a model for the prevention of crime caused by dysfunctional families, juxtaposed with the African practice of the ‘Palaver’, which brings all the community stakeholders in dialogue, to find a permanent solution to crime. Although the study is on SAPCC, the recommendations can be applicable to other church groups who are interested in applying a decolonial perspective to combating crime.